Tolerability and efficacy of the cancer vaccine UV1 in patients with recurrent or metastatic PD-L1 positive head and neck squamous cell carcinoma planned for first-line treatment with pembrolizumab – the randomized phase 2 FOCUS trial - Brandt, Anna; Schultheiss, Christoph; Klinghammer, Konrad; Schafhausen, Philippe; Busch, Chia-Jung; Blaurock, Markus; Hinke, Axel; Tometten, Mareike; Dietz, Andreas; Müller-Richter, Urs; Hahn, Dennis; Alt, Jürgen; et al. (Frontiers in Oncology, 2024)
Background: Globally, head and neck squamous cell carcinoma (HNSCC) is the seventh most common malignancy. Despite aggressive multimodal treatment approaches, recurrent and/or metastatic (R/M) disease develops in >50% of patients. In this setting, pembrolizumab was approved for patients with PD-L1 expression. However, response rates with checkpoint inhibitor monotherapy remain limited and strategies to strengthen tumor-directed immune responses are needed.The FOCUS trial is designed to estimate the effectiveness of UV1 vaccination in combination with pembrolizumab versus pembrolizumab as a single agent in patients with R/M HNSCC.The FOCUS trial is a two-armed, randomized, multicenter phase II study which was designed to evaluate the efficacy and feasibility of the hTERT-targeted cancer vaccine UV1 as add-on to pembrolizumab in the 1st line treatment of patients with R/M PD-L1 positive (combined positive score 1) HNSCC. Secondary objectives are the exploration of patient subgroups most likely deriving benefit from this novel combination and the establishment of liquid biopsy tumor monitoring in HNSCC.